Evolution of an oblique volcanic passive margin: The case of Nuussuaq in West Greenland - Guan, Huixin; Abdelmalak, Mansour M.; Xu, Min; Geoffroy, Laurent (Tectonophysics, 2023)
Most rifted margins involve a certain degree of obliquity. Oblique extension has been well-studied in a magmapoor continental rift setting. However, few studies have addressed the structure and evolution of oblique rifting in a magma-rich continental rift setting. In this study, we used remote sensing and field measurements combined with geophysical data in order to study the tectono-magmatic evolution of seaward-dipping basalt sequences, known also as seaward dipping reflectors (SDRs), along the western Nuussuaq oblique volcanic passive margin. We calculated the directions and dips of lavas within onshore SDRs based on remote sensing and field data and analyzed the offshore SDRs through seismic reflection profiles to obtain a precise 3D structure of the inner SDRs along this margin. Our results show that the development of the inner SDRs can be divided into two stages. During the first stage (the late Paleocene), the oblique extension was partitioned into strike-slip and dip-slip components, and the basalt sequences were mainly bounded by N-S-trending continentward-dipping faults. During the second stage (the early Eocene), a local stress reorientation occurred in the western Nuussuaq and the basalt sequences were mainly bounded by NE-SW-trending continentward-dipping faults. The obliquity of the margin originated from both the reactivation of the inherited Itilli Fault and the magma intrusion into the crust, which weakened the crust and produced a pressure-induced extension orthogonal to the margin.